Corrupção, justiça e o herói trágico no imaginário brasileiro: um estudo dos processos de criação das capas da Revista Veja sobre o personagem Sergio Moro - Esposito, Mauricio Pontes (2021)
The journalistic coverage of Car Wash in Brazil between 2014 and 2019 introduced Sergio Moro, a Federal Court judge in the city of Curitiba, who became a national hero for a portion of Brazilian society and media as fighter against political corruption, a condition that led him to be Minister of Justice and a participant in the national political and legal debate. His role as the main magistrate of the Car Wash Operation was motive of controversy and questioning since the beginning of the investigations, influenced the destiny of national politics and generated debates and reflections in the most varied scientific fields. This doctoral thesis is linked to the line of research “Processes of creation in communication and culture” and investigates how the idea of corruption, justice and the tragic hero in the Brazilian imaginary circulated in communication processes based on an examination of narratives about the character Sergio Moro presented by Veja Magazine on its covers. The discussions are based on studies of the imaginary (DURAND), political scandal (THOMPSON) and network communication (CASTELLS). The method consists of: bibliographic research of scientific studies on the subject; survey and curation of journalistic texts; mapping and choosing recurring topics; in-depth studies on the concepts of imaginary and justice; and analysis based on the proposed cartography of the imaginary (LEÃO), which involves: (1) observation and description of the phenomenon; (2) establishing relationships and agencies that influence him; and (3) interpretation of the phenomenon. The analysis proposes relationships with the hero's journey (CAMPBELL) and the tragic condition of post-modernity (MAFFESOLI). As the results obtained, it was possible to detect how the coverage of the main Brazilian weekly information magazine about the political scandal was guided by the processes of construction of the image of the former judge and former minister as a tragic hero